Murder at Ford's Theatre. - Truman, Margaret (Capital crimes series., 2002)
When the body of a young theatre volunteer named Nadia Zarinski is found in a dark alley, two cops, Rick Klayman and Moses "Mo" Johnson, discover that Nadia was the intern for, and the rumored lover of, an influential right-wing Senator.